Silk fibroin-sodium dodecyl sulfate gelation: molecular, structural, and rheological insights - Hirlekar, Swarali; Ray, Debes; Aswal, Vinod K.; Prabhune, Asmita; Nisal, Anuya; Ravindranathan, Sapna (Langmuir, 2019)
A gelling agent is necessary to accelerate sol to gel transition in an aqueous solution of silk fibroin (SF), which otherwise takes several days to complete. In this paper, we investigate the mechanism of gelation of Bornbyx mori SF by a model anionic surfactant, sodium dodecyl sulfate (SOS). Even though interactions between SDS and proteins have been extensively investigated, most of these studies have focused on globular proteins, which undergo denaturation. The interaction with a fibrous protein such as SF is different and results in an altered secondary structure leading to gelation. In this work, the concentration-dependent gelation process of the SF-SDS system is examined using rheology, SANS, FTIR, and NMR. We observed preferential binding of SDS to specific regions on the SF chain, which aids structural changes favoring beta-sheet formation. We propose a mechanism for the accelerated sol-gel transition in the SF-SDS system.